Understanding Responsible Research Assessment: A MacIntyrean Proposal - Daraio, Cinzia; Maletta, Sante (Acta Philosophica, 2025)
Recently, research evaluation has undergone significant change, driven by the digitization of evaluation processes, the availability of data and the emergence of commercial tools offering readily accessible indicators. Amidst this change, the concept of responsibility has emerged as a central theme. However, its precise meaning remains elusive. In our investigation, we adopt a phenomenological approach to elucidate the notion of responsibility as it pertains to research evaluation. Drawing inspiration from MacIntyre, we scrutinize research practices, examining the challenges posed by external factors and the compartmentalization of social roles. This MacIntyrean philosophical framework, with its emphasis on virtues, allows us to shed light on the complexities of research assessment. Our work represents an initial examination contributing to ongoing debate about the future of research evaluation.